Challenges of Virtual Thai EFL Classes: Times of Pandemics - Cheewala Badklang (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
The Covid-19 pandemic has impacted human life for over two years. To learn to adapt to the new normal era, we have to change the way of living, working, communicating, and so on. Similarly, the educational platform has been changed and most impacted from elementary to tertiary level in Thailand. In this regard, teaching and learning have been conducted on digital platforms. Therefore, this paper aims to recognize the challenges of the virtual EFL classes encountered by Thai instructors of English from a university in the deep south of Thailand during the Covid-19 pandemic. Survey questions were done from the instructors’ perspectives. The challenges of teaching and learning in the virtual EFL classes faced by Thai instructors showed mainly three issues, namely (1) technological issues; (2) pedagogical issues, and (3) personal issues. These three principally issues could be valuable preliminary information for the English department as well as the university management to understand the problems by seeking and providing proper methods for the virtual EFL classroom during the times of pandemics.